Outcomes for women with diabetes admitted for labour care to midwifery units in the UK: a national prospective cohort study and survey of practice using the UK Midwifery Study System (UKMidSS) - Lisa Smith; Rachel Rowe; Alessandra Morelli; Rachel Plachcinski; Wendy Tyler; Amar Karia; Amber Marshall (BMJ Open)
Objectives To describe outcomes in women admitted for labour care to midwifery units with gestational or pre-existing diabetes, compare outcomes with other women admitted to the same units and describe admission and care guidance in midwifery units typically admitting women with diabetes.Design A national cohort study and a survey of practice.Setting We used the UK Midwifery Study System to collect data from midwifery units in the UK between October 2021 and February 2023.Participants Women with a diagnosis of diabetes admitted for labour care to a midwifery unit were compared with a cohort of women without diabetes admitted for labour care to the same units.Primary and secondary outcome measures The primary outcome was a composite measure of maternal outcome reflecting the need for obstetric care (one or more of augmentation, instrumental birth, caesarean birth, maternal blood transfusion, third or fourth-degree perineal tear, maternal admission to higher level care). We also investigated a number of secondary maternal and neonatal outcomes.Results Overall, 420 (0.7% (95% CI 0.67% to 0.82%) of the 56 648 women admitted to midwifery units in the study period were recorded as having diabetes, most (84%) with diet-controlled gestational diabetes. Women with diabetes were no more likely than comparison women to experience the composite primary outcome (18.7% vs 20.7%, adjusted relative risk=1.31, 95% CI 0.96 to 1.80). We found no statistically significant differences between the two groups for the secondary maternal and neonatal outcomes investigated: augmentation, postpartum haemorrhage >1.5 L, shoulder dystocia, maternal blood transfusion and maternal admission for higher level care, Apgar <7 at 5 min, initiation of breast feeding and neonatal unit admission.Conclusions The findings of this study provide evidence that selected women with well-controlled gestational diabetes may safely plan birth in midwifery units on the same site as obstetric and neonatal services. With clear admission criteria and careful care planning, access to a midwifery unit provides an opportunity to increase choice, reduce intervention and improve outcomes for these women.